Sulfinates and thiocyanates triggered 6-endo cyclization of o-alkynylisocyanobenzenes - Onnicha Khaikate (2019)
© The Royal Society of Chemistry. Diverse 2-sulfonyl- and 2-thiocyanato-3-substituted quinolines were synthesized from o-alkynylisocyanobenzenes by nucleophilic addition of the respective sulfinate sodium salts and ammonium thiocyanate to the isocyanide moiety followed by cyclization. The salient features of the methodology include metal-free, ambient temperature and mild reaction conditions, ease of reagent handling, and broad functional group tolerance.